2021
DOI: 10.1111/imr.13024
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulation of B cell receptor signaling

Abstract: microRNAs (miRNAs) are evolutionarily conserved, small non-coding RNAs (ncRNAs) that are crucial in the regulation of a myriad of cellular functions via RNA interference (RNAi). In hematopoietic cell lines, multiple studies describe the impact of miRNAs on lineage determination and maturation. 1,2 Likewise, because miRNAs regulate many important biological pathways in lymphocytes, their deregulation has been implicated in malignant disease and autoimmunity. 3 Transcribed in the nucleus by RNA polymerase II, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 146 publications
0
7
0
Order By: Relevance
“…Therefore, the term "inflamma-miRs" was coined to refer to these miRNAs (Quinn and O'neill, 2011). Further, additional studies have progressively linked miRNAs to the neuroinflammatory signaling, including NF-κB signaling (Amjad et al, 2019), TLR signaling pathway (Paschon et al, 2016), B cell receptor signaling (Borbet et al, 2021), and Jak/Stat signaling (Zhang M. et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the term "inflamma-miRs" was coined to refer to these miRNAs (Quinn and O'neill, 2011). Further, additional studies have progressively linked miRNAs to the neuroinflammatory signaling, including NF-κB signaling (Amjad et al, 2019), TLR signaling pathway (Paschon et al, 2016), B cell receptor signaling (Borbet et al, 2021), and Jak/Stat signaling (Zhang M. et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Endocytosis pathway was the second most significant pathway, and Mycobacterium tuberculosis often invades cells through endocytosis, so this pathway is closely related to the invasion mechanism of Mycobacterium tuberculosis ( 30 ). B cell receptor signaling pathway, an important immune pathway, can regulate the survival, proliferation and differentiation of B lymphocytes ( 31 , 32 ). In addition, we also found that among the six key genes previously screened, TP53 and AKT1 genes were in the herpes simplex virus 1 infection pathway, genes ARF1 and PRKCZ were in the endocytosis pathway, and gene AKT1 was in the B cell receptor signaling pathway, indicating that these four genes all play important regulatory roles in the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are small non-coding RNAs that play crucial roles in post-transcriptional gene regulation. 20,21 miR-378a-3p is a member of the miR-378 family that has been reported to have multiple functions in various biological processes. [22][23][24] Recent studies have indicated that miR-378a-3p is involved in the regulation of osteoblast differentiation and bone formation.…”
Section: Introductionmentioning
confidence: 99%